2019
DOI: 10.1016/j.envexpbot.2019.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning index and non-structural carbohydrate dynamics among contrasting cassava genotypes under early terminal water stress

Abstract: Cassava (Manihot esculenta Crantz.) is a storage root crop of importance in tropical regions where periodic dry season and drought affect performance. Cassava genotypes that differ in performance in ecosystems with various water regimes were subjected to water stress during storage-root initiation and early development. Plants were grown in 50 kg pots in a screen house environment under well-watered and water stress for over a 120-day period. Water stress had a significant effect on most traits analyzed. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Connor et al (1981) 7 showed that under water deficit, the proportion of assimilates routed to the roots increased. Sustained root growth and thus allocation of assimilates to roots under dry conditions was also noted as a favourable trait for increased cassava production under water stressed conditions 20 …”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Connor et al (1981) 7 showed that under water deficit, the proportion of assimilates routed to the roots increased. Sustained root growth and thus allocation of assimilates to roots under dry conditions was also noted as a favourable trait for increased cassava production under water stressed conditions 20 …”
Section: Introductionmentioning
confidence: 96%
“…Sustained root growth and thus allocation of assimilates to roots under dry conditions was also noted as a favourable trait for increased cassava production under water stressed conditions. 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mostly grown in tropical and subtropical areas (Alves, 2002;Li et al, 2016 andWang et al, 2018). Cassava is reasonably drought tolerant and is expected to be highly adaptable to future climate change, making it an important crop for food security (Jarvis et al, 2012;Duque and Setter, 2019). Cassava is Africa's fourth largest source of calories (FAO, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance on drought associated with high efficiency in the use of nutrients (Fernandes et al, 2019) makes the crop key for both food security and subsistence for developing nations (Duque & Setter, 2019). Cassava is a highly profitable crop and has good production in cultivation systems (Barata et al, 2021).…”
Section: Introductionmentioning
confidence: 99%